2005
DOI: 10.1158/1078-0432.ccr-04-2062
|View full text |Cite|
|
Sign up to set email alerts
|

Combining a Recombinant Cancer Vaccine with Standard Definitive Radiotherapy in Patients with Localized Prostate Cancer

Abstract: Purpose: Many patients with clinically localized prostate cancer develop biochemical failure despite excellent local therapy perhaps due to occult metastatic disease. One potential solution is the utilization of a well-tolerated systemic therapy (e.g., vaccine) in concert with local therapy. Experimental Design:We present a randomized phase II clinical trial designed to determine if a poxviral vaccine encoding prostate-specific antigen (PSA) can induce a PSA-specific T-cell response when combined with radiothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
250
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 338 publications
(256 citation statements)
references
References 46 publications
6
250
0
Order By: Relevance
“…2,[5][6][7] On the other hand, while there is evidence that RT generates 'danger' signals that might mature dendritic cells (DCs) to present tumor antigen 8,9 there is no good evidence that this occurs in the clinic and such signals may be too weak to be effective. In a recent randomized phase II clinical trial study, 10 addition of recombinant vaccine administration to standard RT in patients with clinically localized prostate cancer showed that vaccination was safe and the generation of a PSAspecific cellular immune response was enhanced following RT. We have shown in previous studies that expression of interleukin-3 (IL-3) gene within tumors can enhance the immunogenicity of even classically nonimmunogenic tumors, 11 without altering their intrinsic radiosensitivity, and this enhances the effects of radiation therapy (RT), allowing a long-term state of immunity to develop after the primary tumor regresses.…”
Section: Introductionmentioning
confidence: 99%
“…2,[5][6][7] On the other hand, while there is evidence that RT generates 'danger' signals that might mature dendritic cells (DCs) to present tumor antigen 8,9 there is no good evidence that this occurs in the clinic and such signals may be too weak to be effective. In a recent randomized phase II clinical trial study, 10 addition of recombinant vaccine administration to standard RT in patients with clinically localized prostate cancer showed that vaccination was safe and the generation of a PSAspecific cellular immune response was enhanced following RT. We have shown in previous studies that expression of interleukin-3 (IL-3) gene within tumors can enhance the immunogenicity of even classically nonimmunogenic tumors, 11 without altering their intrinsic radiosensitivity, and this enhances the effects of radiation therapy (RT), allowing a long-term state of immunity to develop after the primary tumor regresses.…”
Section: Introductionmentioning
confidence: 99%
“…The abscopal effect (when local radiotherapy is associated with regression of metastatic cancer at a distant site) has been seen in the setting of checkpoint blockade (26,27). The rationale for combining radiotherapy with immunotherapy is to induce an in situ vaccine effect, leading to antigenic spread, uptake of antigens, maturation of DCs, and activation of T cells (28). Like radiation, chemotherapy causes direct cell killing and induction of ICD (29).…”
Section: Discussionmentioning
confidence: 99%
“…Radiation in combination with cancer vaccines has been found to kill tumor cells effectively [12,13]. Radiation is known to kill cancer cells via its direct cytotoxic effect and via the induction of radiation-induced immune response [1,14,15].…”
Section: Discussionmentioning
confidence: 99%